Prediction of significant prostate cancer diagnosed 20 to 30 years later with a single measure of prostate-specific antigen at or before age 50. - Lilja, H; Cronin, A; Dahlin, A; Manjer, J; Nilsson, P; Eastham, J; Bjartell, A; Scardino, P; Ulmert, D; Vickers, A (2011)
BACKGROUND: We previously reported that a single prostate-specific antigen (PSA) measured at ages 44-50 was highly predictive of subsequent prostate cancer diagnosis in an unscreened population. Here we report an additional 7 years of follow-up. This provides replication using an independent data set and allows estimates of the association between early PSA and subsequent advanced cancer (clinical stage ≥T3 or metastases at diagnosis). METHODS: Blood was collected from 21,277 men in a Swedish city (74% participation rate) during 1974-1986 at ages 33-50. Through 2006, prostate cancer was diagnosed in 1408 participants; we measured PSA in archived plasma for 1312 of these cases (93%) and for 3728 controls. RESULTS: At a median follow-up of 23 years, baseline PSA was strongly associated with subsequent prostate cancer (area under the curve, 0.72; 95% CI, 0.70-0.74; for advanced cancer, 0.75; 95% CI, 0.72-0.78). Associations between PSA and prostate cancer were virtually identical for the initial and replication data sets, with 81% of advanced cases (95% CI, 77%-86%) found in men with PSA above the median (0.63 ng/mL at ages 44-50). CONCLUSIONS: A single PSA at or before age 50 predicts advanced prostate cancer diagnosed up to 30 years later. Use of early PSA to stratify risk would allow a large group of low-risk men to be screened less often but increase frequency of testing on a more limited number of high-risk men. This is likely to improve the ratio of benefit to harm for screening.